The Relationship Between Environmental Commitment and Managerial Perceptions of Stakeholder Importance - Henriques, Irene; Sadorsky, Perry (Academy of Management Journal, 1999)
Do firms committed to stewardship of the natural environment differ from less environmentally committed firms in their perceptions of the relative importance of different stakeholders in influencing their environmental practices? Using cluster analysis on six responses to questions describing a firm's practices, we classified 400 firms into four environmental profiles: reactive, defensive, accommodative, and proactive. Results indicate that firms with more proactive profiles do differ from less environmentally committed firms in their perceptions of the relative importance of different stakeholders.